Knowledge, Attitude, and Practice of Medical Students Regarding Anger - Maleeha Iqbal, Rashid Ahmad, Shama Iqbal, Abdul Samad, Nizaqat Ullah, Javaria Imtiaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Anger is a strong emotional response to deprivation and provocation. It is an emotion that is often created by the discrepancy between our expectations and reality. For medical professionals, it is very necessary to manage their anger because they have to deal with patients of diverse manners. The current study aimed to evaluate the knowledge, attitude and practices of medical students regarding anger from an Islamic perspective. Methods: the current study enrolled medical students who were enrolled in different grades in medical schools. Moreover, after the informed consent, each student was asked to fill out the self-designed questionnaire. The data was statistically analysed by SPSS. Results: The study population comprised 277 subjects, including females and males. Among all participants in the current study, females (147, 53.1%) are more common than males. The highest and lowest numbers of students are enrolled in the 1st year of MBBS (74, 26.7%) and the final year of MBBS (1, 0.4%), respectively. Moreover, personal behaviour after getting angered was asked, like do you leave the scene (said Yes, 123, 44.4%) or seek refuge with Allah (said Yes, 92, 33.2%) from shaitan or taking ablution (said No, 54, 19.5%). The p-value is less than 0.05 for the questions asked as anger is satanic teaching or motivation (p=0.004), or Islam has refrained us from anger (p=0.000), and anger results in an increased crime rate (p=0.000). Similarly, the p-value is less than 0.05 in the case of questions like do you get irritated soon (p=0.002) and when did you get angry (p=0.001). Conclusion: It is concluded that young medical students are more aggressive, and they have less ability to manage their aggressiveness. Islamic teaching plays a vital role in the management and control of anger. Keywords: Medical Students, Anger Management, Knowledge, Islamic Teachings.